Simulación de los mínimos de interacción de cafeína con las bases de los ácidos nucleicos y sus rutas de transición - Deriabina, A.; Cruz, A.; González, E.; Grokhlina, T. I.; Poltev, V. I. (Revista Mexicana de Ingenieria Biomedica, 2004)
Caffeine has an influence on an extended set of biological processes. To explain molecular mechanisms of this influence, we are performing calculations of the interaction energy of caffeine molecule with nucleic acid fragments via molecular mechanics methods. The calculations reveal three types of mutual caffeine-base and caffeine base pair arrangements corresponding to the energy minima. Besides well-known stacking arrangements, two other types of mutual positions of molecules in minima have been found; corresponding to planar and perpendicular arrangements with caffeine-base hydrogen bond formation. They are possible for both nucleic acid monomers and DNA duplexes. The calculations suggest a possible influence of caffeine on DNA interactions with biologically active molecules via complex formation with basepairs and ligands.